High efficiency Raman memory by suppressing radiation trapping. (3rd July 2017) - Thomas, S E; Munns, J H D; Kaczmarek, K T; Qiu, C; Brecht, B; Feizpour, A; Ledingham, P M; Walmsley, I A; Nunn, J; Saunders, D J
Abstract: Raman interactions in alkali vapours are used in applications such as atomic clocks, optical signal processing, generation of squeezed light and Raman quantum memories for temporal multiplexing. To achieve a strong interaction the alkali ensemble needs both a large optical depth and a high level of spin-polarisation. We implement a technique known as quenching using a molecular buffer gas which allows near-perfect spin-polarisation of over 99.5 % in caesium vapour at high optical depths of up to ∼ 2 × 10 5 ; a factor of 4 higher than can be achieved without quenching. We use this system to explore efficient light storage with high gain in a GHz bandwidth Raman memory.